Identifying Risk Factors Associated With False‐Negative Results in US‐Guided Percutaneous Transthoracic Needle Lung Biopsy of Subpleural Pulmonary Lesions - Jiawei Yi; Mengjun Shen; Junhui He; Runhe Xia; Xinyu Zhao; Yin Wang (Thoracic Cancer)
ABSTRACT Background This study aims to investigate the factors influencing false‐negative results in ultrasound‐guided percutaneous transthoracic needle lung biopsy results (US‐PTLB). Materials and Methods This ambispective cohort study included patients with subpleural pulmonary lesions who underwent US‐PTLB with benign pathological findings between April 2017 and June 2022 (retrospective cohort) and between July 2022 and October 2022 (prospective cohort). In the retrospective cohort, comparative and logistic regression analyses were performed to identify independent risk factors for false‐negative biopsy results. Stratified analyses based on these risk factors were performed in the prospective cohort. Results The retrospective cohort included 1747 (true‐negative: false‐negative, 1321:426) patients with negative biopsy results, which were analyzed by comparative and logistic regression analyses, and the results demonstrated that advanced age (> 56 years) (OR = 1.08, 95% CI: 1.07–1.09), small‐sized lesions (< 3 cm) (OR = 1.80, 95% CI: 1.38–2.34), lesions with necrosis (OR = 3.00, 95% CI: 2.29–3.92), contrast‐enhanced ultrasound (CEUS) showing hyper‐enhancement (OR = 5.87, 95% CI: 4.09–8.42) or iso‐enhancement (OR = 2.81, 95% CI: 2.05–3.83), and the presence of hemoptysis (OR = 11.82, 95% CI: 5.16–27.08) or pneumothorax (OR = 7.90, 95% CI: 2.89–21.58) during the puncture were independent predictors of false‐negative US‐PTLB results. The results of stratified analyses in the prospective cohort were consistent with the retrospective cohort. Conclusion Risk factors associated with false‐negative results included advanced age (> 56 years), small‐sized lesion (< 3 cm), presence of necrosis in the lesion, CEUS showing hyper‐enhancement or iso‐enhancement of the lesion, and hemoptysis or pneumothorax during puncture. Trial Registration: Number: ChiCTR2000029749